YouTube Searches for Anterior Cruciate Ligament Injury Promote Biased, Low-Quality Videos. Issue 12 (2020) - Ward, Brittany; Lin, Alex; Lin, Jasmine; Warren, Christopher; Mattern, Patrick; Paskhover, Boris; Chu, Alice
ABSTRACT: Purpose: YouTube is the second most accessed website worldwide and is increasingly used by patients to search for medical knowledge. This study aims to evaluate the bias and overall quality of anterior cruciate ligament (ACL) YouTube videos. Methods: A list of 40 videos was compiled using the terms "ACL tear" and "ACL reconstruction." The DISCERN criteria, which utilizes a 5-point Likert scale, was used to evaluate the bias and overall quality of each and assign a DISCERN score (DS). The presence of a US board-certified orthopedic surgeon, publisher type, publication date, number of views, and video length were recorded. Additional ACL videos on the websites of the American Orthopaedic Society for Sports Medicine and the American Academy of Orthopaedic Surgeons were rated using DISCERN. Results: Mean bias DS for "ACL reconstruction" was 1.85 ± 1.57, and that for "ACL tear" was 2.30 ± 1.78. Mean overall quality DS was 2.05 ± 1.19 for "ACL reconstruction" and 2.00 ± 1.12 for "ACL tear." Unique videos received 25, 198, 961 total views and were an average of 6.83 ± 7.20 min and 5.61 ± 3.21 yr old. Most videos were posted by hospitals, followed by companies. Fifty-three percent of videos included commentary by US-board certified orthopedic surgeons, and the bias and overall quality DS were significantly higher than the remaining videos ( P < 0.05). Videos from the American Orthopaedic Society for Sports Medicine and American Academy of Orthopaedic Surgeons had a bias DS of 3.00 ± 0.00 and overall DS of 2.00 ± 0.00. Discussion: The general public does not have access to unbiased, high-quality ACL injury videos, despite an increasing need for access to educational videos. Physicians and professional societies are educated resources who can help increase public access and availability to unbiased, high-quality video medical information online.